Enhancing Samhong Cultivation: Boosting Plant Growth with Fermented Cow Urine and EM4-Molasses Blend: Peningkatan Budidaya Samhong: Meningkatkan Pertumbuhan Tanaman dengan Pemanfaatan Urin Sapi Fermentasi dan Campuran EM4-Molase - Kholifah, Nur; Miftakhurrohmat, A (Indonesian Journal of Innovation Studies, 2023)
This study investigates the utilization of fermented cow urine with EM4 and molasses to enhance plant growth in Samhong cultivation. The main objective is to explore the interaction between concentration and interval of bovine urine fertilization. The research was conducted in the Janjing field, Trawas district, Mojokerto Regency, from October to December 2022, using a randomized block design with two factors. The first factor consisted of three levels: 20 ml/l, 40 ml/l, and 60 ml/l of bovine urine concentration, while the second factor comprised three intervals of fertilization: every 2 days, every 4 days, and every 6 days. Results indicate that the concentration of bovine biourine did not significantly affect all variables. Notably, the best fertilization interval of every 4 days (I2) demonstrated improved plant height (20.50 cm), leaf count (10.74), fresh weight (77.67 grams), and dry weight (9.74 grams). Additionally, a significant interaction was observed between concentration and bovine urine fertilization interval, with the highest number of leaves found in the 60 ml/l concentration treatment at an interval of 4 days (12.42 strands), and the widest leaf area recorded in the 20 ml/l concentration treatment at an interval of 2 days (118.76 cm²). Highlights: Utilization of fermented cow urine with EM4 and molasses can increase plant growth: The study suggests that adding fermented cow urine with EM4 and molasses can have a positive effect on plant growth. This finding could be of interest to farmers and researchers looking for alternative fertilizers that can promote plant growth. The best fertilization interval is every 4 days: The study found that the interval of fertilization has an impact on plant growth, with the best result observed with fertilization every 4 days. This information could be useful for farmers and researchers looking to optimize their fertilization schedule. Significant interaction between concentration and biourine fertilization interval of cattle: The study found a significant interaction between the concentration and the biourine fertilization interval of cattle, indicating that the optimal concentration of biourine and fertilization interval are dependent on each other. This information could be relevant for farmers and researchers who are interested in developing a customized fertilization plan for their crops. Keywords: Bovine Urine Fertilization, EM4, Fermented Cow Urine, Molasses, Plant Growth